One Health risk challenges and preparedness regarding bovine tuberculosis at abattoirs in North-central Nigeria: Associated drivers and health belief. - Ismail Ayoade Odetokun; Nma Bida Alhaji; Jibrin Aminu; Mohammad Kabir Lawan; Madinat Abimbola Abdulkareem; Ibraheem Ghali-Mohammed (Public Library of Science (PLoS), 2022)
Background Bovine tuberculosis (bTB) is a serious public health and neglected zoonotic disease responsible for 147,000 human cases and 12,500 deaths annually. This study assessed knowledge, risk perceptions, and preventive practices regarding bTB among occupationally exposed abattoir workers and drivers for transmission in slaughterhouses. Methods Using a pre-tested questionnaire, we surveyed a cross-section of workers in five main abattoirs in North-central Nigeria between 2018 and 2019. Data were analysed using descriptive statistics and univariable/multivariable logistic regression analyses at a 95% confidence level. Results All recruited respondents (n = 422: 77.7% meat processors and 22.3% meat and sanitary inspectors) participated and 10.4% had no formal education. About 44.0% and 27.0% of workers knew about bTB occurrence at the abattoirs and its transmission to humans, respectively. Less than one-third use personal protective equipment (PPE) during meat handling, only a few workers correctly practised routine handwashing, and 21.8% sterilized meat handling tools. A few participants (6.4%) had BCG vaccination against tuberculosis. Demographic characteristics (age, gender, occupation, and formal education) significantly influenced the perception and practices about bTB. A few workers perceived raw meat and milk, direct contact with infected carcasses, organs and contaminated fomites, contaminated environment through infected blood, dirty slaughtering floor, and aerosols of contaminated faeces as high-risk bTB transmission routes. Perceived drivers that influenced bTB transmission at abattoirs include unhygienic meat processing (OR = 5.4, 95%CI = 3.1-9.4, p < 0.001) and non-enforcement of abattoir standard operating systems (OR = 10.4, 95%CI = 6.0-18.5, p = 0.001). Conclusion The workers have low knowledge levels, perceptions, and practices toward bTB emergence. These demand the workers' education on hygienic meat handling to mitigate the menace of the disease. Surveillance and preventive preparedness considering the identified drivers through the 'One Health' approach are recommended.